Basic physiological measures determine fitness and are associated with running performance in elite young male and female Ethiopian runners - Legaz Arrese, A.; Kinfu, H.; Munguia-Izquierdo, D.; Carranza-Garcia, L. E.; Calderon, F. J. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: The aim of this study was to determine if possible, with the resources available in Ethiopia, to make significant associations between racing performance and laboratory physiological test results in elite young African runners. METHODS: Twenty-four young Ethiopian runners (12 males and 12 females) attended the physiology laboratory of the Addis Ababa University, where skin fold thickness, basic resting pulmonary function and heart rate (HR) during an incremental treadmill exercise test were recorded a week before or a week after two official 800 and 1500 meter races. Performance was rated according to the scoring procedures of the International Association of Athletics Federations (IAAF): male runners (1041, CV=4.1%), female (1051, CV=2.8%). RESULTS:The sum of four skin folds was significantly correlated with male (r=-0.80, P<0.01) and female IAAF score (r= -0.78, P<0.01). IAAF score was also related to forced vital capacity (male: r=0.70, P<0.05; female: r=0.85, P<0.01) and forced expiratory volume in 1 s (male: r=0.63, P<0.05; female: r=0.80, P<0.01). For both sexes, HR at a fixed submaximal exercise workload was significantly associated with IAAF score. In both male and female runners, the more significant association was observed for a treadmill slope of 7.5% (r=-0.93, P<0.01; r= -0.95, P<0.01, respectively). CONCLUSIONS: These results show that basic physiological measures are useful in measuring fitness and in predicting middle-distance running performance in a homogeneous group of elite young male and female Ethiopian runners.